Immunologic effects on peripheral lymphoid cells from patients with chronic hepatitis type B during administration of recombinant interleukin 2. - Yamaguchi, S (1988)
Nine patients with chronic hepatitis type B were treated with recombinant interleukin 2 (rIL-2). Side effects were limited to low-grade fever and headache, which were transient and tolerable for the patients. Seven normal volunteers and nine patients with chronic active hepatitis were administered by one bolus of 500 units of rIL-2. Acute effects of rIL-2 administration on lymphoid cells included a rapid decrease in lymphocytes, especially in cytotoxic T cells and natural killer cells. These acute effects resolved within 24 hours. There was no difference in the changes of immunological parameters between normal volunteers and patients. The same effects were seen during 28 days of rIL-2 administration. The number of lymphocytes and CD4 positive cells was increased after rIL-2 administration for 28 days (P less than 0.01). Natural killer cell activity, especially that of CD16+ and Leu-7- cells was also increased (P less than 0.05). These effects may favour the elimination of virus-infected hepatocytes.